Effects of KCl and CaCl2 on the evolution of anhydro sugars in reaction intermediates during cellulose fast pyrolysis. (1st September 2019) - Leng, Erwei; Costa, Mário; Gong, Xun; Zheng, Anqing; Liu, Shijun; Xu, Minghou
Graphical abstract: Highlights: The effects of KCl and CaCl2 on the evolution of anhydro sugars were explored. The catalytic effects of KCl were weakened by the low degree of polymerization. KCl showed a stronger effect on the reducing end than on the levoglucosan end. CaCl2 strongly promoted secondary reactions of reaction intermediates. Abstract: Reaction intermediates mainly consisting of anhydro sugars are the crucial transitional stage connecting the cellulose feedstock and the three phases of products during pyrolysis. For the first time, the effects of KCl and CaCl2 on the evolution of anhydro sugars in reaction intermediates were examined by using levoglucosan pyranose (LGA_Pyran), maltosan and cyclodextrin as model compounds. These compounds were subjected to fast pyrolysis on a Py-GC/MS, where dry samples were heated at a heating rate of 10 °C/s to 500 °C with a holding time of 20 s at 500 °C. The results indicated that KCl had a stronger inhibitory effect than CaCl2 on LGA_Pyran formation during cellulose fast pyrolysis. However, during the pyrolysis of the oligosaccharides, the catalytic effects of KCl were weakened by the low degree of polymerization and the lack of reducing ends, while the catalytic effects of CaCl2 were enhanced by a better distribution. This led to the reverse order of their effects on LGA_Pyran formation. Furthermore, much higher char yields from oligosaccharides under catalysis of CaCl2 than under the catalysis of KCl indicate the prominent influence of CaCl2 on the secondary reactions of reaction intermediates leading to secondary char.